IMPLEMENTASI KESEPAKATAN GLOBAL MIGRASI DAN POLYMORPHIC DI INDONESIA DALAM PERSPEKTIF KEIMIGRASIAN - Seno, Andhika Ario; Romdoni, Doni; Ibrahim, Maulana Malik; Winanto, Indra; Jeferson, Mauritz Richard (Polteknik Imigrasi, 2024)
This research examines the implementation of the Global Compact for Safe, Orderly, and Regular Migration and the application of the polymorphic approach in the context of immigration in Indonesia. The Global Migration Agreement offers a framework to ensure safe and legal migration. The research results show that Indonesia has implemented several important principles, such as protecting migrant rights and strengthening international cooperation. However, challenges are still found in inter-institutional coordination and regional policy alignment. It is hoped that this research will provide insight for the government and related institutions in optimizing migration policies in Indonesia which are in line with international standards.